The Ligament of Marshall: Far From Vestigial! - Raghav Chandra, MD; Jasmina Ehab, MD; Madhuri Nagaraj, MD; Suresh Keshavamurthy, MD (Annals of Thoracic Surgery Short Reports)
Background: The ligament of Marshall (LOM) is a vestigial fold of the left atrium that contains the remnant left cardinal vein, muscle bundles, and nerve fibers. Despite its description as an embryologic remnant, the LOM carries significant clinical importance as an important focus for atrial fibrillation propagation as well as a therapeutic target. Methods: In this review, we discuss the embryologic origins of the LOM, its physiology and importance in atrial fibrillation pathogenesis, as well as the role of targeting and ablating the LOM surgically during concomitant cardiac surgery including lung transplantation. Results: The LOM, particularly its distal segment, is an important focus for atrial fibrillation as both a primary trigger as well as an accessory bundle for signal propagation. It is a key target for electrophysiologic therapies including radiofrequency and alcohol-based ablative strategies. The LOM is also a crucial target for surgical ablation while addressing the left atrial lesion sets. This is often performed concomitantly with other cardiac surgical operations and may play an important role in reducing the risk of postoperative atrial fibrillation after lung transplantation. Conclusions: Far from just a vestigial structure, the ligament of Marshall remains an important focus for paroxysmal atrial fibrillation and is a potent therapeutic target for both electrophysiologic and surgical approaches.